مستوى معرفة معلمي الحلقة الأولى من التعليم الأساسي في محافظة دمشق بصعوبات القراءة والكتابة لدى التلاميذ - عماد حسن; المحمود عبد الحي عبد الكريم (Latakia University Journal - Arts and Humanities Sciences Series, 2013)
هدف البحث التعرف إلى مستوىً معرفة معلمي الحلقة الأولى من التعليم الأساسي بصعوبات القراءة والكتابة في محافظة دمشق, ومعرفة دلالة الفروق في مستوىً معرفة المعلمين, تبعاً لمتغير البحث (الدورات التدريبية), وتكونت عينة البحث من (152) معلماً ومعلمة, تم اختيارهم بالطريقة القصدية من مدارس محافظة دمشق الرسمية, حيث طُبق عليهم استبانتي المعرفة بصعوبات القراءة والكتابة, وهما من إعداد الباحث بعد التحقق من صدقهما وثباتهما. وأشارت النتائج إلى ما يلي: وجود مستوىً منخفض من المعرفة لدى معلمي الحلقة الأولى من التعليم الأساسي بصعوبات القراءة حيث ظهرت نسبة المعرفة فيها (%37,91). وجود مستوىً منخفض من المعرفة لدى معلمي الحلقة الأولى من التعليم الأساسي بصعوبات الكتابة حيث ظهرت نسبة المعرفة فيها (%36,89). وجود فروق ذات دلالة إحصائية في مستوىً معرفة معلمي الحلقة الأولى من التعليم الأساسي بصعوبات القراءة, تبعاً لمتغير الدورات التدريبية, لصالح المعلمين الخاضعين لدورات تدريبية. وجود فروق ذات دلالة إحصائية في مستوىً معرفة معلمي الحلقة الأولى من التعليم الأساسي بصعوبات الكتابة, تبعاً لمتغير الدورات التدريبية, لصالح المعلمين الخاضعين لدورات تدريبية. This research aims at acquainting with the level of teachers’ knowledge in thefirst stage in basic learning of reading and writing disabilitiesin Damascus Government and knowingthe significance of differences on the level of teachers`knowledge according to the variable of training Courses. The sample of the study consisted of (152) teachers who were selected purposelyfrom the official schools in Damascus governorate. Twoquestionnaires were applied on this sample, related to the knowledge reading and writing disabilities, and prepared by the researched after they were tested for theirvalidity and reliability. This research comes up with the following results: There was a low level of knowledge at first stage teachers in basic learning of reading disabilitiesand the rate was (%37, 91). There was a low level of knowledge at first stage teachers in basic learning of writingdisabilitiesand the rate was (%36, 89). There were statistical significant differences at the knowledge level of first stage teachers in basic learning of reading disabilitiesaccording to the variable of training courses, on the side of teachers` who followed training courses. There were statistical significant differences at the knowledge level of first stage teachers in basic learning of writing Disabilitiesaccording to the variable of training courses, on the side of teachers` who followed training courses.